PENGARUH KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN PUSKESMAS RAWAT INAP HARUYAN KECAMATAN HARUYAN KABUPATEN HULU SUNGAI TENGAH - Raudah, Siti (Al Iidara Balad, 2020)
In the Haruyan Health Center, Haruyan Sub-District, Hulu Sungai Tengah Regency, the number of patients who have been served both outpatient and inpatient throughout 2019 reached 12749 patients. The purpose of this study is to uncover, analyze and predict the magnitude of the effect of the quality of health services on patient satisfaction at the Haruyan Health Center, Haruyan District, Hulu Sungai Tengah District. The method used is quantitative research that is intended to provide a clear picture of the problems under study in interpreting and explaining data systematically. The basis of this research is a survey, which is the distribution of questionnaires to respondents containing questions about matters relating to the quality of health services in the Haruyan Inpatient Health Center Haruyan District Hulu Sungai Tenga Regency. From the results of the study showed that the quality of health services affect patient satisfaction in the Haruyan Health Center with Tangibles dimensions in the form of physical services, Reliability dimensions namely service officers, Resvonsivbess dimensions namely responses from service officers, Assurance dimensions namely in the form of service guarantee for patients, and the Empathy dimension, namely the care of service officers to patients so far can provide patient satisfaction at the Haruyan Inpatient Health Center. The advice given for input material is to provide a place for consultation and complaints of problems in service, adding medical personnel such as general practitioners, specialists, medicine and administrative officers in the service, further increasing the exception or responsiveness of service personnel to patient complaints .